Pengaruh Pertumbuhan Aset, Ukuran Perusahaan, Nilai Tukar, dan Suku Bunga terhadap Nilai Perusahan pada Perusahaan Food & Beverage di Bursa Efek Indonesia - Firna Dao; Rafiqah Asaff; Arini Lestari Aris; Suryati Syam; Mursida Mursida (Universitas Andi Djemma, 2022)
This research aims to find out the effect of asset growth, company size, exchange rate and interest rates on company value (empirical study on food and beverage companies listed on the Indonesia Stock Exchange for the period 2017-2019). The growth of assets and the size of the company is an internal factor of the company, while the exchange rate and interest rates are external factors of the company. The population of this study amounted to 28 companies and the determination of samples using purposive sampling methods with predetermined criteria and produced 15 research samples. For the data analysis method used is multiple regression by looking at the F test, t and R² test. The results of this study showed that asset growth had no effect on the value of the company, the size of the company had no effect on the value of the company, the exchange rate had no effect on the value of the company.